THE CONCEPT OF NASKH MANSUKH TEUKU MUHAMMAD HASBI AL-SHIDDIQIE: A SOCIOLOGICAL OVERVIEW OF KNOWLEDGE (QS ANALYSIS. ALBAQARAH: 106 IN THE TAFSIR AN-NUR) - Fithrotin; Wangi, Baiti Sekar; Fadlillah, Fadlillah (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
The concept of naskh–mansūkh (abrogation) has long remained one of the most contested issues in ʿUlūm al-Qurʾān, particularly with regard to its methodological legitimacy and epistemological implications in Qur’anic interpretation. This study critically examines the construction of naskh–mansūkh in Hasbi al-Shiddiqie’s interpretation of Qur’an 2:106 in Tafsir an-Nur by employing Karl Mannheim’s sociology of knowledge as its analytical framework. The primary objective of this research is to uncover how the meaning of naskh is produced, negotiated, and reconfigured within the socio-intellectual context of post-independence Indonesia. Adopting a qualitative-descriptive design grounded in library research, the study applies discourse analysis to Qur’anic exegesis, situating the interpretive text within the historical position of the exegete and the dynamics of Islamic intellectual tradition. Primary data are drawn from Tafsir an-Nur, supported by classical exegetical sources, Hasbi al-Shiddiqie’s intellectual writings, and theoretical works on the sociology of knowledge. The findings demonstrate that Hasbi al-Shiddiqie does not conceptualize naskh–mansūkh as the literal annulment of Qur’anic rulings or texts, but rather as a process of contextualization and semantic reconciliation aimed at preserving the enduring normative relevance of revelation. From a Mannheimian perspective, this interpretive stance reflects a pattern of relationism, in which the meaning of naskh emerges through a dialectical engagement between classical exegetical authority and the social demands of modern Indonesian society. This study argues that naskh–mansūkh in Tafsir an-Nur represents a socially situated intellectual construction that embodies an effort toward exegetical reform without undermining the authority of the Qur’anic text. By doing so, the article contributes to Indonesian Qur’anic studies and advances broader discussions on the interplay between interpretation, social context, and epistemic authority in Islamic scholarship.